A twenty-segment kinematics and kinetics model for analysing golf swing mechanics - Ferdinands, R. E. D.; Kersting, U. G.; Marshall, R. N. (Sports Technology, 2013)
The golf swing is a complex, multi-planar, three-dimensional (3D) motion sequence performed at very high speeds. These properties make biomechanical analysis of the golf swing difficult. Hence, the aim of this study was to develop a computer model of the golf swing capable of calculating a diverse range of 3D kinematics and kinetics values based on motion analysis data collected in the laboratory. Five golfers performed six swings in the field of view of eight Falcon High Speed Resolution cameras (240 Hz), which captured the movements of 56 markers placed on the golfers and their clubs, resulting in marker trajectories that were processed into linear xyz-coordinates using the Eva Motion Analysis system. To perform the kinematics and kinetics calculations, a 20-segment rigid body model of the human body was designed in the Mechanical Systems Pack, connecting the segments by a selection of linear and spherical constraints, resulting in a system of segments with 58 degrees of freedom, with the constraint equations of motion calculated by the Newton-Lagrangian iteration method. The model allowed for the derivation of segmental sequencing, separation angles, segmental planes of motion, segmental velocity contributions, joint torques and muscle powers. The preliminary data suggest that such an integrated kinematics and kinetics analysis is necessary to understand the mechanical complexity of golf swing. Even with the small sample size analysed in this study, some interesting trends were found, such as certain violations of the classical proximal-to-distal sequencing scheme, differing swing plane and club head trajectories in the backswing and downswing phases, minimal hip angular velocity contribution to the ball at impact, concentric and eccentric muscle powers in the downswing phase, and increased lumbar loading factors from the mid-downswing phase to ball impact.